Informacijski sistem nujne medicinske pomoči v Sloveniji - Fink, Andrej (Informatica Medica Slovenica, 2006)
In the past year, with consideration of the future renewal of the organizationand infrastructure of the Emergency Unit of the Ljubljana University Medical Center, we conducted analysis of the current condition of emergency medical services and we created a complete scheme for a new information system in emergency medicine within the Ljubljana University Medical Center. The information system scheme was designed in the way that theconcepts can also be used in other hospitals or emergency medicine units throughout the country. Within the scope of this project the telemonitoring solution has been put to the test, namely the electronic transmission of the urgent patient data. The system for basic telemedicine services has been set up in pre-hospital settings and four different locations within the Ljubljana University Medical Center.
Keywords: Ambulances; Emergency Medical Service Communication Systems; Emergency Medical Services; Reševalni avtomobili; Urgentna, medicinska služba, komunikacijski sistemi; Urgentne, medicinske službe